Komparasi Efisiensi Penghimpunan Dana Pihak Ketiga Bank Umum Syariah Dan Bank Umum Konvensional Di Indonesia Dengan Metode Data Envelopment Analysis - Yuliati Yuliati; Noven Suprayogi (Universitas Airlangga, 2016)
This study aims to determine and comparing the level of third-party funds accumulation efficiency of Islamic Banks and Conventional Banks in Indonesia. This study uses a quantitative non-parametric approach with Data Envelopment Analysis (DEA) CRS and VRS assumption, and statistical tool namely Mann Whitney U-Test. The samples are 10 Islamic Banks and 13 Conventional Banks those comply with the specified sample criteria. During 2010 to 2014, Islamic Banks has efficiency level of third-party funds accumulation relatively higher than Conventional Banks based on CRS and VRS assumption. Source of inefficiency in Islamic Banks is the scale of third-party funds accumulation. While the hypothesis test showed there was no significant difference in the level of third-party funds accumulation efficiency between Islamic Banks and Conventional Banks in Indonesia with the assumption of CRS, VRS, and Scale efficiency.